Determining factors in the use of Instagram for consumption intention (Dimensión Empresarial, 2020)
Social networks are proving to be a strategic instrument of competitive advantage. The study aims to analyze the influence between the frequency of use, the perceived utility and the ease of use of Instagram in relation to the consumer's intention to buy. An online survey was conducted with 262 users. The data were interpreted using exploratory factor analysis and multiple linear regression to determine the relationship between the respective factors. The results showed that the frequency of use, the perceived utility and the ease of use have a positive effect on the intention to buy through Instagram.